Strengthening and Transformation of the Islamic Education System in Malaysia - Suhid, Asmawati (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
AbstractEducation is an important aspect in fulfilling the mission and human development agenda. Hence, Islam places great importance in education as was stated in the first verse revealed to the Prophet Muhammad (PBUH). In Malaysia, education is also a priority in the country’s development including Islamic education. The Islamic Education System in Malaysia is constantly evolving and changing in order to meet the needs and demands of the society. Parents and societies who are increasingly interested and realised the importance of Islamic education have created various forms and types of Islamic education. As an example, the emergence of Maahad Tahfiz, Ulul Albab programme, private Islamic Schools, Darul Quran and the J-QAF programme showed a very encouraging improvement. Attention is also given to the children of young prisoners and married teenagers in order they are not left behind in the mainstream education. Hence, this paper will discuss the development, strengthening and transformation of the Islamic education system in Malaysia besides highlighting some research findings that support this discussion. Abstrak Pendidikan merupakan aspek penting dalam memenuhi misi dan agenda pembangunan manusia. Oleh karena itu, Islam menekankan pentingnya pendidikan seperti Firman dalam ayat pertama yang diwahyukan kepada Nabi Muhammad (SAW). Di Malaysia, pendidikan juga menjadi prioritas dalam pembangunan negara termasuk pendidikan Islam. Sistem Pendidikan Islam di Malaysia terus berkembang dan berubah untuk memenuhi kebutuhan dan tuntutan masyarakat. Orang tua dan masyarakat yang semakin tertarik dan menyadari pentingnya pendidikan Islam telah menciptakan berbagai bentuk dan jenis pendidikan Islam. Sebagai contoh, munculnya Pesantren Tahfiz, Program Ulul Albab, Sekolah Islam swasta, Darul Quran dan program J-QAF menunjukkan peningkatan yang sangat menggembirakan. Perhatian juga diberikan kepada tahanan anak-anak dan remaja yang sudah menikah agar mereka tidak tertinggal dalam meraih pendidikan pada umumnya. Oleh karena itu, dalam artikel ini penulis akan membahas tiga topik utama; pengembangan, penguatan dan transformasi sistem pendidikan Islam di Malaysia. Dalam rangka mendukung diskusi, beberapa temuan penelitian akan disorot.How to Cite : Suhid, A. (2018). Strengthening and Transformation of The Islamic Education System in Malaysia. TARBIYA: Journal of Education in Muslim Society, 5(1), 66-77. doi:10.15408/tjems.v5i1.9511.